An exploration of the views of paramedics regarding airway management. Issue 1 (December 2016) - Brandling, Janet; Rhys, Megan; Thomas, Matthew; Voss, Sarah; Davies, Sian Emma; Benger, Jonathan
Abstract Background Paramedics are a skilled group of clinicians with expertise in airway management. Our research group has completed a trial comparing supraglottic airway devices with tracheal intubation during out of hospital cardiac arrest. This is a contentious topic amongst paramedics in the United Kingdom (UK). We explored the customs and beliefs of UK paramedics in relation to airway management, and whether tracheal intubation contributes to and sustains paramedic professional identity. Methods The study took place within South Western Ambulance Service NHS Foundation Trust. We used a qualitative approach, conducting interviews and focus groups with paramedics. The themes arising from interviews were discussed in focus groups, developing a deeper understanding and providing insight and recommendations for future research and policy. Purposive sampling accounted for differing training and for participation in the main trial. There were 17interviews and five focus groups with a further 17 participants. Data saturation was achieved. Results Four domains were identified. Pride - The ability to use a life-saving skill in austere conditions. Utility - Different training routes and experience have led to different attitudes towards airway management. Inconsistent expectations - Paramedics felt that there were different perceptions of their abilities amongst hospital staff and the general public. Professionalization - Debate over airway management is not founded on good evidence. Conclusion We have demonstrated that UK paramedics have a wide range of views regarding airway management, and that these are based on evidence and experience rather than dogma. Airway management contributes to paramedics' professional identity, but is not reliant on this.